The effect of the term auction facility on the London inter-bank offered rate - James McAndrews; Asani Sarkar; Zhenyu Wang (Federal Reserve Bank of New York, 2008)
This paper examines the effects of the Federal Reserve's Term Auction Facility (TAF) on the London Inter-Bank Offered Rate (LIBOR). The particular question investigated is whether the announcements and operations of the TAF are associated with downward shifts of the LIBOR; such an association would provide one indication of the efficacy of the TAF in mitigating liquidity problems in the interbank funding market. The empirical results suggest that the TAF has helped to ease strains in this market.
Keywords: G10; G12; G18; G19; 330; LIBOR; liquidity; money markets; Term Auction Facility